Kidney involvement in rheumatoid arthritis - A. Icardi; P. Araghi; M. Ciabattoni; U. Romano; P. Lazzarini; G. Bianchi (PAGEPress Publications, 2003)
Rheumatoid Arthritis (RA) is a widespread disease and its renal involvement, relatively common, is clinically significant because worsens course and mortality of the primary disease. There is still no agreement on the prevalence of renal disorders in RA: data analysis originates from different sources, as death certificates, autopsies, clinical and laboratory findings and kidney biopsies, each with its limitations. Histoimmunological studies on bioptical specimens of patients with RA and kidney damage, led to clarify prevalent pathologies. In order of frequency: glomerulonephritis and amyloidosis (60-65% and 20-30% respectively), followed by acute or chronic interstitial nephritis. Kidney injury during RA includes secondary renal amyloidosis, nephrotoxic effects of antirheumatic drugs and nephropathies as extra-articular manifestations (rheumatoid nephropathy). Amyloidosis affects survival, increases morbidity and is the main cause of end stage renal disease in patients with RA and nephropathy. Strong association between RA activity and amyloidosis needs the use of immunosuppressive and combined therapies, to prevent this complication and reduce risk of dialysis. Long-lasting and combined RA pharmacotherapy involves various renal side effects. In this review we describe NSAIDs and DMARDs (Disease-Modifying Antirheumatic Drugs) nephrotoxicity, particularly by gold compounds, D-penicillamine, cyclosporine A and methotrexate. Rare cases of IgA glomerulonephritis during immunomodulating therapy with leflunomide and TNF blocking receptor (etanercept) are reported; real clinical significance of this drug-related nephropathy will be established by development of RA treatment. In RA nephropathies, mesangial glomerulonephritis is the most frequent histological lesion (35-60 % out of biopsies from patients with urinary abnormalities and/or kidney impairment), followed by minimal change glomerulopathy (3-14%) and p-ANCA positive necrotizing crescentic glomerulonephritis.